Elucidating the complex hydrolysis and conversion network of xanthan-like extracellular heteropolysaccharides in waste activated sludge fermentation - Chen-Yuan Zhou; Kun Dai; Yi-Peng Lin; Xing-Chen Huang; Yan-Lin Hu; Xuan-Xin Chen; Xiao-Fei Yang; Qi-Yuan Sun; Yong Zhang; Mark C.M. van Loosdrecht; Raymond Jianxiong Zeng; Fang Zhang (Water Research X)
The hydrolysis of structural extracellular polymeric substances (St-EPS) is considered a major limiting step in the anaerobic fermentation of waste activated sludge (WAS). However, the degradation of heteropolysaccharides, characterized by complex monomers of uronic acids and neutral saccharides in St-EPS, has rarely been reported. In this study, microbial-produced xanthan-like heteropolysaccharides, characterized by a blue filamentary film, were identified. The xanthan-producing bacteria comprised ∼7.2% of total genera present in WAS. An xanthan-degrading consortium (XDC) was enriched in an anaerobic batch reactor. This consortium could degrade Xanthan for over 90% and disrupt the gel structure of xanthan while promoting methane production from WAS by 29%. The xanthan degradation network consisting of extracellular enzymes and bacteria was elucidated by combining high-throughput sequencing, metagenomic, and metaproteomic analyses. Five enzymes were identified as responsible for hydrolyzing xanthan to monomers, including xanthan lyase, β-d-glucosidase, β-d-glucanase, α-d-mannosidase, and unsaturated glucuronyl hydrolase. Seven genera, including Paenibacillus (0.2%) and Clostridium (3.1%), were identified as key bacteria excreting one to five of the aforementioned enzymes. This study thus provides insights into the complex conversions in anaerobic digestion of WAS and gives a foundation for future optimization of this process.